Effects of Biodiesel from Soybean Oil on the Exhaust Emissions of a Turbocharged Diesel Engine: Effects of Biodiesel on Exhaust Emissions of Diesel Engine - Shah, Asad Naeem; shan, G. E. Yun-; wei, TAN Jian-; Chao, He (Biological Sciences - PJSIR, 2009)
This paper presents the regulated emissions in the light of cylinder pressure and heat release rate (HRR) from a 4-stroke direct injection (DI) diesel engine fuelled with neat soybean oil-based biodiesel, commercial diesel and 20% biodiesel-diesel blend. The engine was run using electrical dynamometer at four different engine conditions. The experimental results revealed that brake power (BP) of the engine decreased but brake specific fuel consumption (BSFC) increased with biodiesel as compared to diesel. Relative to diesel, the maximum combustion pressure (MCP) was higher; however, HRR curves were not much deeper in the ignition delay (ID) periods and the premixed combustion peaks were lower with biodiesel. Carbon monoxide (CO), total hydrocarbons (HC), smoke opacity, and particulate matter (PM) emissions decreased by 3% to 14%, 32.6% to 46%, 56.5% to 83%, and 71% to 87.8%, respectively; however, oxides of nitrogen (NO ) increased by 2% to 10% with biodiesel, compared to the commercial diesel. Both smoke and NO pollutants were greatly influenced by the MCP. CO, HC, and PM emissions were higher at lower load conditions compared to higher load conditions, but NO and smoke pollutants were higher at higher load conditions relative to lower load conditions.